An Analysis on Fragile People of a Local Government Strategic Between Malaysia and Thailand in Time of Covid-19 Pandemic - et. al., Non Naprathansuk, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article aimed to analyzed and compared on fragile people of a local government strategics between Malaysia and Thailand in time of Covid-19 pandemic. The methodology of this article was a qualitative approach based on the secondary data from case of Malaysia and Thailand. The finding of this article was Malaysia’s local government has more independent and design different business and social strategies to help fragile people consist of community care initiative, homeless people assistance and business scheme opportunity for petty traders and hawkers rather than Thai’s government that local government did not have fully autonomous authorities and independent from Thai government. Therefore, the contribution of this article up to enlighten the roles and functions of the local government as fundamental institution to assist and support the local fragile and vulnerable people in facing the pandemic crisis of COVID-19..